Mentalizing oneself: detecting reflective functioning in life narratives. Issue 4 (4th July 2019) - Köber, Christin; Kuhn, Magdalena Maria; Peters, Isabel; Habermas, Tilmann
ABSTRACT: Reflective functioning (RF) is defined as the ability to infer mental states of others and oneself. While RF has been predominantly studied in attachment research, it might also occur in other autobiographical narratives because of its strong connection to self-organization and self-understanding. Therefore, this study took a first step combining research on RF with developmental narrative research. In a longitudinal lifespan study covering up to three measurements across 8 years and six age groups ( N = 172), we aimed to detect RF in entire life narratives to explore its development with age and its contribution to causal-motivational coherence of life narratives. Although scores were initially low, RF could be identified in life narratives, and was found to develop throughout adolescence and to predict life narrative coherence above and beyond age. Results confirm RF as significantly contributing to narrative self-organization, indicating promising new paths in research on autobiographical narratives and self.